Estudo da produção de etanol de sacarose por fermentação extrativa utilizando arraste com dióxido de carbono - Sonego, Jorge Luiz Silveira (2016)
The ethanol accumulated in the broth during fermentation is the main component toxic to yeast, causing slower yeast growth and decreased ethanol production. One way of overcoming this inhibition effect is to use extractive fermentation, where the ethanol is removed from the broth during the fermentation process. The present work evaluated sucrose ethanol production using extractive fermentation using CO2 as stripping gas. Firstly, it was made investigation of the influence of specific CO2 flow rate, initial ethanol concentration and solution temperature on ethanol stripping by CO2. At this stage the modeling of the of ethanol and water removal was achieved by CO2 stripping according to a first order model. In sequence, it was studied the production of ethanol by extractive fermentation in batch and fed-batch modes, employing in a 5 L bubble column bioreactor and temperature of 34.0 °C. The kinetic parameters of the hybrid Andrews-Levenspiel model were estimated by modeling of conventional batch and fed-batch fermentations (without stripping) with CS0 of 180 g.L-1. Mathematical modeling of extractive in batch and fed-batch ethanol fermentation was developed considering the removal of ethanol and water, due to the CO2 stripping, according to a first order model. Later it was optimized the production of ethanol by extractive fed-batch fermentation. A genetic algorithm was used to simultaneous optimization the substrate feed rate (F) and the ethanol concentration (CE0) to start CO2 stripping in extractive fed-batch fermentation, so as to obtain the maximum ethanol productivity. The ethanol removal by stripping with carbon dioxide can be modeled as a first order model. The hybrid model of Andrews-Levenspiel was adequate to describe the kinetics of batch and fed batch ethanol fermentation. The proposed model for extractive ethanol fermentation with CO2 was adequate to describe the behavior of extractive fermentation in batch and fed batch modes. In the extractive ethanol fermentation with CO2 stripping an increase in substrate uptake rate (rS=−dCs/dt) after the beginning of ethanol stripping and the total consumption of the substrate occurred before the extractive fermentation compared to the conventional process. The extractive batch fermentation with CS0=180 g.L-1 and CO2 stripping initiated after 3 h of fermentation at an ethanol concentration of 43.3 g.L-1, resulted in an ethanol productivity (in g.L-1.h-1) about 25% higher than conventional batch fermentation. For fed-batch fermentation, vat filling time (Ft) of 5 h and start of ethanol stripping at 3 h of fermentation substantially reduced the inhibitory effects of the substrate and ethanol on the yeast cells. This condition enabled the extractive fed-batch ethanol fermentation to be performed using substrate concentrations of up to 240 g.L−1 in the feed. The total ethanol concentration reached 110.3 g.L−1 (14 °GL) (wine + entrained). The use of the optimization tool enabled using substrate concentrations of up to 300 g.L-1 generating a total concentration of ethanol of 17.2 °GL (wine + entrained), which means an increase of 65% compared to the concentration final ethanol obtained in conventional fermentation without stripping.